2010
DOI: 10.1309/ajcpwy1sgj9ieaor
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Follicular Lymphoma to Plasmablastic Lymphoma With c-myc Gene Rearrangement

Abstract: Follicular lymphoma (FL) is an indolent lymphoma that transforms to high-grade lymphoma, mostly diffuse large B-cell lymphoma, in about a third of patients. We present the first report of a case of FL that transformed to plasmablastic lymphoma (PBL). Clonal transformation of the FL to PBL was evidenced by identical IGH/BCL2 gene rearrangements and VDJ gene usage in rearranged IGH genes. IGH/ BCL2 translocation was retained in the PBL, which also acquired c-myc gene rearrangement. Genealogic analysis based on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…STAT1 had a low expression level in DN-p38 JB6 Cl41 cells in Table 2 and we already confirmed that STAT1 was the downstream of p38 MAP kinase and regulated JB6 Cl41 cell transformation. Many studies show that myc proto-oncogene mediates cell transformation (Bapat et al, 2010;Figueiredo et al, 2010;Ouansafi et al, 2010;Sablina et al, 2010). Our data showed myc proto-oncogene had low expression level in EGF-stimulated DN-p38 JB6 Cl41 cells and this result indicates that myc proto-oncogene also played a role in EGF-induced JB6 Cl41 cell transformation and it should be the downstream of p38 MAP kinase.…”
Section: U58533supporting
confidence: 49%
“…STAT1 had a low expression level in DN-p38 JB6 Cl41 cells in Table 2 and we already confirmed that STAT1 was the downstream of p38 MAP kinase and regulated JB6 Cl41 cell transformation. Many studies show that myc proto-oncogene mediates cell transformation (Bapat et al, 2010;Figueiredo et al, 2010;Ouansafi et al, 2010;Sablina et al, 2010). Our data showed myc proto-oncogene had low expression level in EGF-stimulated DN-p38 JB6 Cl41 cells and this result indicates that myc proto-oncogene also played a role in EGF-induced JB6 Cl41 cell transformation and it should be the downstream of p38 MAP kinase.…”
Section: U58533supporting
confidence: 49%
“…Secondary PBL transformed from chronic lymphocytic leukemia or FL also frequently harbor MYC translocations. 83,84 All of these observations suggest that MYC aberrations do also play a role in the pathogenesis of aggressive lymphoid neoplasms with terminal B-cell differentiation. This finding is remarkable because most aggressive B-cell lymphomas with MYC rearrangements have a GC phenotype.…”
Section: Dh/th Lymphomamentioning
confidence: 99%
“…PBL is associated with rearrangements in the c-MYC gene in more than 40 % of cases [42,43]. Valera and colleagues reported c-MYC rearrangement in 50 % of the cases reviewed and noted that EBV positive patients are more likely to have the c-MYC abnormality and cmyc rearrangement occurs less frequently in EBV negative patients [44].…”
Section: Cytogenetic Analysismentioning
confidence: 99%